Development of a genome-wide InDel marker set for allele discrimination between rice (Oryza sativa) and the other seven AA-genome Oryza species - Hechanova, Sherry Lou; Bhattarai, Kamal; Simon, Eliza Vie; Clave, Graciana; Karunarathne, Pathmasiri; Ahn, Eok-Keun; Li, Charng-Pei; Lee, Jeom-Sig; Kohli, Ajay; Hamilton, Ruaraidh Sackville; Hernandez, Jose E.; Gregorio, Glenn B.; et al. (MDPI, 2021)
Wild relatives of rice in the genus Oryza (composed of 24 species with 11 different genome types) have been significantly contributing to the varietal improvement of rice (Oryza sativa). More than 4000 accessions of wild rice species are available and they are regarded as a “genetic reservoir” for further rice improvement. DNA markers are essential tools in genetic analysis and breeding. To date, genome-wide marker sets for wild rice species have not been well established and this is one of the major difficulties for the efficient use of wild germplasm. Here, we developed 541 genome-wide InDel markers for the discrimination of alleles between the cultivated species O. sativa and the other seven AA-genome species by positional multiple sequence alignments among five AA-genome species with four rice varieties. The newly developed markers were tested by PCR-agarose gel analysis of 24 accessions from eight AA genome species (three accessions per species) along with two representative cultivars (O. sativa subsp. indica cv. IR24 and subsp. japonica cv. Nipponbare). Marker polymorphism was validated for 475 markers. The number of polymorphic markers between IR24 and each species (three accessions) ranged from 338 (versus O. rufipogon) to 416 (versus O. longistaminata) and the values in comparison with Nipponbare ranged from 179 (versus O. glaberrima) to 323 (versus O. glumaepatula). These marker sets will be useful for genetic studies and use of the AA-genome wild rice species.